Tinjauan Yuridis Penerapan Pajak Karbon sebagai Solusi Percepatan Green Energy di Indonesia - Nadia Nathania Sutanto; Dinda Devina Maharati; Syahreza Fachran (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2023)
Environmental issues are receiving special attention in the international community, including Indonesia. Therefore, to realize this commitment, the Government of Indonesia plans to develop a Carbon Economic Value through a carbon tax. This research aimed to provide government input to accelerate the realization of green energy through carbon pricing with a carbon tax mechanism. The type of research conducted in this research uses normative legal research, namely legal research conducted by examining literature or secondary data. The results of this study indicate that the Government of Indonesia still needs to fully prepare to implement a carbon tax, both from a legal standpoint, the implementation mechanism, to the readiness of the people and their economic conditions. Therefore it takes significant steps by the Indonesian Government to make specific regulations to regulate carbon emissions, including the application of carbon taxes and the transition to the use of green energy. With this regulation, Indonesia will realize net zero emissions and a positive domino effect that affects various aspects of Indonesian society.